2013
DOI: 10.1111/iej.12094
|View full text |Cite
|
Sign up to set email alerts
|

Use of cone‐beam computed tomography to evaluate C‐shaped root canal systems in mandibular second molars in a Turkish subpopulation: a retrospective study

Abstract: The configuration of C-shaped canals varied along the length of the root. The prevalence of C-shaped canals in mandibular second molars in this Turkish population was lower than in other Asian populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
52
3
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(80 citation statements)
references
References 27 publications
16
52
3
1
Order By: Relevance
“…In the present study, most of the teeth with Cshaped canals were grooved in the buccal direction, which contrasts with the results by Helvacioglu-Yigit and Sinanoglu, 9 Jin et al 14 and Zheng et al 20 However, these authors evaluated Turkish, Korean and Chinese populations, respectively. This could represent another anatomical variation related to ethnicity.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In the present study, most of the teeth with Cshaped canals were grooved in the buccal direction, which contrasts with the results by Helvacioglu-Yigit and Sinanoglu, 9 Jin et al 14 and Zheng et al 20 However, these authors evaluated Turkish, Korean and Chinese populations, respectively. This could represent another anatomical variation related to ethnicity.…”
Section: Discussioncontrasting
confidence: 99%
“…As indicated from the aforementioned studies, there is a strong relation between this type of anatomic variation and the characteristics of the population from which the sample was selected. 2,[8][9][10][11][12][13][14][15] We also encourage more studies to be conducted to determine the prevalence of anatomical variations in different ethnic groups, especially those that have not been evaluated previously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17] In a study conducted on a group of Turkish inhabitants, the prevalence of C-shaped root canals in mandibular second molars was found to be 8.9%. 20 However, previous studies reported that C-shaped canal morphology was not observed in mandibular first molars in the same population. 21,22 In the present case report, a C-shaped root canal morphology occurence in a mandibular first molar and its endodontic treatment were described.…”
Section: Discussionmentioning
confidence: 86%
“…Recently, computed tomography (CT) was used for the observation of root canal systems (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). CT can be applied in patients whose gender and age are identified, and without tooth extraction.…”
Section: Introductionmentioning
confidence: 99%